Optimasi dan Pemodelan Proses Recover Flavor Dari Limbah Cair Industri Pengolahan Rajungan Dengan Reverse Osmosis - . Uju; Bustami Ibrahim; Wini Trilaksani; Tati Nurhayati (Jurnal Ilmu Pertanian Indonesia, 2009)
The waste water of blue crab pasteurization has potential in environmental pollution. It contained TSS of 206.5mg.1-1, BOD 7,092.6mg.1-1 and COD of 51,000mg.1-1. on the other hand, it also contains an interesting flavor compound, which composed of 0.23% non protein nitrogen and 17 amino acids where the highest was glutamic acid one. In this study, pre-filtration step using filter size 0.3 µ followed by reverse osmosis has been used to reduce these pollutions load and flavor compound recovery. During pre-filtration steps, TSS was reduced to 74.8% so turbidity decrased reased until 31%. After reverse osmosis process, BOD, and COD decreased more than 99%, and there was no amino acids detected in permeate stream. Factors that affect performance of reverse osmosis were transmembrane pressure, temperature and pH. The higher transmembrane pressure, temperature and pH resulted the higher the flux permeate. The use of higher temperature make flux increasing, eventually increasing transmembrane pressure make the flux increased only at transmembrane pressure less than 716 kPa. The protein rejection was influenced unsignifanctly by transmembrane pressure, temperature and pH. During concentrating flux declined exponentially by time function. At concentration factor 2.75 resulted 79% and 12% of increasing protein and NPN, respectively. The amino acids content can be increased 2−23 times of the origin. Even arginin and sistin, the amino acids that were undetectable initially, but they can bedetected at concentration of 0.0360 and 0.0250 (w/v) respectively at the end of the process. Hidrolysis and fermentation process can increase the amino acid content 31−45 times.